Engineering Change Orders Design Using Multiple Variables Linear Programming for VLSI Design. (24th August 2014) - Fan, Yu-Cheng; Lin, Chih-Kang; Chou, Shih-Ying; Wang, Chun-Hung; Wu, Shu-Hsien; Liu, Hung-Kuan
Abstract : An engineering change orders design using multiple variable linear programming for VLSI design is presented in this paper. This approach addresses the main issues of resource between spare cells and target cells. We adopt linear programming technique to plan and balance the spare cells and target cells to meet the new specification according to logic transformation. The proposed method solves the related problem of resource for ECO problems and provides a well solution. The scheme shows new concept to manage the spare cells to meet possible target cells for ECO research.